Anxiety sensitivity in online gamers - Kahraman, Beyza; Kaya Yertutanol, Fatma Duygu (Journal of Dependence, 2021)
Objective: The aim of this study was to examine the levels of game addiction and anxiety sensitivity in young adults who play online games. Method: The study was conducted cross-sectionally on the sociodemographic data form, the Anxiety Sensitivity Index and the Game Addiction Scale Short Form, which were delivered to volunteers who reported that they played online games through an online research platform. Game addiction was evaluated according to the monothetic and polythetic formats of the scale. Results: 7.8% of the 438 participants are game addicts according to the Game Addiction Scale Short Form monothetic format, and 40.9% are game addicts according to the polythetic format. Anxiety sensitivity levels in game addicts are higher than in non-game addicts. Anxiety sensitivity is higher in women. According to the monothetic format, game addiction does not differ in terms of age, gender, marital status and educational status, and according to the polythetic format, game addiction is higher in undergraduate and widow/divorced individuals. Conclusion: As a trait-like factor, anxiety sensitivity may lay the groundwork for game addiction. The relationship between anxiety sensitivity and problematic game playing needs to be examined in more detail to screen depression and anxiety disorders.